Successful treatment with ivabradine in a β‐blocker‐refractory patient with acute decompensated heart failure with reduced ejection fraction - Tomoko Inoue; Keiji Matsunaga; Waki Kobayashi; Tetsuo Minamino (Clinical Case Reports)
Abstract Ivabradine is an established treatment for chronic heart failure with reduced ejection fraction (HFrEF); however, it is not used for acute heart failure treatment. Negative inotropic effects (NIE) often limit the up‐titration of β‐blockers. Contrarily, ivabradine has no NIE, and enables β‐blockers usage for treating patients with acute decompensated HFrEF.